Cookies based on apple pomace (Malus domestica Borkh) and rice flour (Oryza sativa L.) - Ana Caroline da Silva Simões; Alba Regina Pereira Rodrigues; Breno Pereira de Paula; Mabelle Biancardi Oliveira de Medeiros (Ciência Rural)
ABSTRACT: In apple juice production, a pomace, rich in fibers and technological properties such as thickening, gelling, and stabilizing capacities, is generated. Considering economic and environmental factors, utilizing this residue is advantageous, presenting an opportunity to add value and enhance the nutritional content of products. Biscuits are widely accepted bakery products with high demand, standing out in the development of food products with enhanced nutritional value. Therefore, this research aimed to develop gluten-free biscuit formulations based on the use of apple pomace and rice flour. To achieve this, apple pomace obtained after juice extraction was dried and milled to reduce its particle size, producing a flour that underwent physicochemical analysis for characterization. Subsequently, three biscuit formulations were prepared: a control formulation with 100% rice flour, one with 25% substitution by apple pomace flour, and one with 50% substitution. The biscuits were analyzed for their growth and subjected to sensory analysis. The apple pomace flour exhibited physicochemical characteristics within standards, being classified as fine, indicating its potential in the enrichment of bakery products. Among the produced biscuits, the formulation with 25% apple pomace flour substitution stood out positively in the sensory evaluation. Additionally, it is recorded higher preference in terms of texture, odor, flavor, and overall evaluation, revealing a notably higher acceptance by consumers. Thus, it is evident that the 25% apple pomace formulation has considerable market potential, securing consumer approval. The incorporation of apple pomace flour proved to be a promising alternative for enriching gluten-free biscuits.